THE ROLE OF STYLISTIC DEVICES IN SHAPING TONE AND MEANING IN MODERN ENGLISH PROSE - Ma’rufova Diyorakhon,; G’ofurova S. M., (TADQIQOTLAR, 2026)
Abstract. This article examines the role of stylistic devices in shaping tone and meaning in modern English prose. It explores how linguistic and literary techniques such as metaphor, irony, symbolism, and alliteration contribute to the expressive power of  texts.  The  study  highlights  the  ways  in  which  authors  use  stylistic  devices  to influence readers’ perception, evoke emotions, and construct deeper layers of meaning. Special  attention  is  given  to  the  pedagogical  importance  of  stylistic  analysis  in understanding literary works and improving language competence.